การสร้างประชาสังคมโดยรัฐ : การปรับตัวของรัฐไทย - สุรางค์รัตน์ จำเนียรพล (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
To study the adaptation process of the Thai state by dominating the ideology and the development of civil society. The main assumption is that amidst the demand for decentralization, the Thai state has adapted itself in order to maintain the power and status quo by overtaking the roles in building civil society. The thesis finds that the state has used the ideology of civil society as a mechanism to protect its status quo. This is clearly seen in the cases of the National Committee for Economic and Social Development Board Office (NESDB) and the Ministry of Interior. There was a discursive competence between the state and the civic groups led by Thai activists and non-governmental organizations (NGOs). The state has won over this discursive competence because of the theoretical weakness embedded in the Thai activists s civil society dominant discourse. This weakness allowed the state to take over the role of building civil society. As a result, civil society has become a part of the state and easily manipulated and dominated by state agencies. In addition, the state now has the authority to redefine the ideology and reshape civil society, and push it into the dominant discourse in Thailand. In terms of discursive practice, the Thai civil society movement has been divided into two groups: pro-state or state-supported group and anti-state group. This divide will ultimately result in the weakness and the fall of the movement.